Curator of Culture - Bushkanets, Liya (Slavica, 2024)
In 2024 we celebrate the 80th birthday of Professor Zoltán Hajnády. The articles in this issue of Slavica have been written by his colleagues to express their respect for him and his work. In addition to the international significance of Zoltán Hajnády’s research on Tolstoy, which is the main focus of his articles, the laudation introducing the series of articles also mentions a broader aspect of his work on Russian–European relations and reveals his deep personality. A representative of humanistic values, a great educator and scientist, he works for the mediation and mutual enrichment of Russian–Russian and Hungarian cultures. For this endeavour, Hajnády was honoured with the Pushkin Medal in 2006.